2012
DOI: 10.1021/jo201910g
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation of β-Hydroxy Hydroperoxides

Abstract: A β-hydroxy hydroperoxide was obtained through base catalyzed disproportionation of a hydroperoxy endoperoxide available by singlet oxygenation of cyclohepta-1,4-diene. Vitamin E and C induce fragmentation of this β-hydroxy hydroperoxide generating aldehydes, especially in the presence of redox active metal ions such as those present in vivo, e.g., under conditions of “iron overload”. This chemistry may contribute to the oxidative cleavage of polyunsaturated fatty acyls that produces similar aldehydes, which d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…The disproportionation of endoperoxide 253 promoted by triethylamine affords β- and γ-hydroxy hydroperoxides 254 and 256 . Under these conditions, the reaction afforded oxodiol 255 and diketone 257 , which cyclized to hemiketal 258 as the products ( Scheme 79 ) [ 354 ].…”
Section: Reviewmentioning
confidence: 99%
“…The disproportionation of endoperoxide 253 promoted by triethylamine affords β- and γ-hydroxy hydroperoxides 254 and 256 . Under these conditions, the reaction afforded oxodiol 255 and diketone 257 , which cyclized to hemiketal 258 as the products ( Scheme 79 ) [ 354 ].…”
Section: Reviewmentioning
confidence: 99%
“…The cleavage pathway from 27 to nopinone may proceed by the well-documented β -hydroxy hydroperoxide fragmentation reaction. 54,55 If our hypothesis is correct, this pathway should also produce peroxy ester 28 as a byproduct, a compound we have not isolated to date. We have, however, observed small amounts (~5%) of dione 30 56 in reactions utilizing the Co(acac) 2 /PhSiH 3 system, conditions which also produce nopinone (Table 2, entry 4).…”
Section: Resultsmentioning
confidence: 87%
“…Early works showed that these species can undergo acid‐ [36] or base‐catalyzed [37] decomposition to give a variety of carbonyl compounds. More recently, Zhang and Salomon have investigated the fragmentation of hydroperoxide species in water under physiological conditions [38] . The authors have shown that the combination of vitamin C and metal cations such as Fe 3+ and Cu 2+ can give aldehydes (as hydrated form) with up to 66 % yield.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, Zhang and Salomon have investigated the fragmentation of hydroperoxide species in water under physiological conditions. [38] The authors have shown that the combination of vitamin C and metal cations such as Fe 3 + and Cu 2 + can give aldehydes (as hydrated form) with up to 66 % yield. While studying the oxidative cleavage of olefins to carboxylic acids, Venturello and coworkers have also shown that an aliphatic β-hydroxy hydroperoxide can decompose at 85°C in the presence of a quaternary ammonium dioxoperotungstate.…”
Section: Thermal Cleavage Of Fatty β-Hydroxy Hydroperoxidesmentioning
confidence: 99%